Immediate postpartum management of patients with severe hypertensive disorders of pregnancy: pathophysiology guiding practice. (19th May 2022) - Hogg, James P.; Szczepanski, Jamie L.; Collier, Charlene; Martin, James N.
Abstract: Developing clinically-focused evidence and experience-based approaches to improve maternity care is a national priority. Safety and quality collaborative initiatives related to management of hypertensive disorders of pregnancy are vital in the implementation of improved care. We reviewed the obstetric literature to construct a concise summary of the core pathophysiologic issues, practice principles and clinical interventions which are foundational for physicians providing immediate postpartum care for patients with severe pregnancy-related hypertension (including those with eclampsia, HELLP syndrome, and superimposed preeclampsia inclusive of those with gestational hypertension that develop severe range blood pressures). While based largely upon the American College of Obstetrics and Gynecology (ACOG) Hypertension Task Force Guidelines released in 2013 as well as updated 2018 guidelines set forth by ACOG for hypertensive disorders of pregnancy, this summary goes beyond the basic safety bundles for hypertension management and lays a pathophysiologic foundation for the immediate postpartum care of patients with severe hypertensive disorders of pregnancy.